Fatwa versus modernity within the philosophical epistemology of the Qur’an: striking a balance between the two - Chiroma, Magaji; Arifin, Mahamad; Abdullah, Mohamad Asmadi; Ansari, Abdul Haseeb (2014)
Nowadays in modern Muslim countries, fatwa (Islamic legal opinion) has been used to harmonize Islamic doctrines and ideologies with modern developments. This has gone far in sharpening the Islamic law administration in some jurisdictions. Fatwa is an instrument that exhibits dynamism of Islamic law in line with the Maqasid ash-Shari’ah (the objectives of Shari’ah). It clarifies some fix issues in the society without compromising the fundamental principles of Shari’ah. Thus, sometimes it has been considered as a tool for modernization, hence to some extent, it is perceived as pro- modernity. Some people failed to understand the objective of fatwa in Islam and how does it function in the society. They do not demarcate between the role of fatwa and the modernity so called. Neither do they distinguish even the Islamic modernization (civilization) from the modernization in the western perspective. It is against this backdrop that the paper, by examining the philosophical epistemology of the Glorious Qur’an, which is the primary source of Shari’ah and guidance (Huda) to mankind, concluded that the concept of fatwa is not aimed at modernization so- called, rather, it is an instrument that confirms the dynamism of Islam and Islamic law. Hence, it is advisable to look at it from the positive perspective rather than the negative perspective.